Noncognitive Indicators as Critical Predictors of Students' Performance in Dental School. Issue 12 (1st December 2015) - Stacey, D. Graham; Kurunathan, Tania M.
Abstract : Dental educators have traditionally prioritized cognitive indicators (especially undergraduate grade point average and Dental Admission Test scores) in choosing students for admission to dental school. These indicators' role in predicting academic outcomes, including coursework and examination success, is well documented. However, noncognitive predictors including conscientiousness, self‐discipline, achievement‐striving, task orientation, deliberation, resilience, and situational judgment have also been identified. This study's aims were to assess the significance of noncognitive indicators measured by the version of the Neuroticism‐Extraversion‐Openness Personality Inventory (NEO PI) known as the NEO‐PI‐3, determine the place in the curriculum when these indicators' impact was most influential, and compare their influence with that of the cognitive indicators. Analysis was performed on stored data for three classes of dental students from admission through clinical exams at one U.S. dental school. Significant associations were found between NEO‐PI‐3 domains and facets (especially Conscientiousness) and the outcomes of coursework grades, standardized exam scores, and clinical behavior scores. Multiple regression analyses identified that the noncognitive indicators enhanced the prediction of students' academic and clinical performance early in the curriculum and then equaled or surpassed the predictive impact of cognitive indicators as they progressed through the curriculum sequence. The implications of noncognitive predictors for dental education are discussed including the challenge to identify and then weight the indicators, whether to include them as admissions criteria, how to assess their impact as compared with cognitive measures, the necessity of standardization of assessment, and if and when to evaluate their relevance to professional practice.